An Analysıs of A Child First Language Acquisition: A Case Study of Phonetic System of A Child 2,3 Years Old - Nurlaillatul Barokah; Muhamad Nandang Sunandar (Universitas Mathla'ul Anwar Banten, 2025)
The aim of this research was to examine the language acquisition of a child 2.3-year-old in terms of phonology, morphology, and syntax. The method used in this study is a qualitative method with a descriptive approach. The subject of this study was a child named Restu Novrizal Ilman. The study focused on analyzing Restu’s first language acquisition, specifically in the areas of phonology, morphology, and syntax. In the syntactic analysis, the researcher examined three types of sentences frequently used by Restu namely interrogative, declarative, and imperative sentences. Based on the analysis of these three linguistic components, the result showed that Restu has demonstrated good language development. Although he is not yet able to form complete morphemes consistently, his speech is generally understandable.